A Case Study Performance Analysis of Design-Build and Integrated Project Delivery Methods. Issue 1 (2nd January 2021) - Adamtey, Simon A.
ABSTRACT: For an owner, choosing the appropriate project delivery method is one of the most important decisions to make for a project. Although there is a plethora of studies on these delivery methods, there is limited research comparing the alternative delivery methods with each other to determine the best methods for different construction projects. The objective of this study was to provide an overview on Design-Build and Integrated Project Delivery while comparing their performance on the construction of two transmission control building facilities. Using a comparative case study analysis, both qualitative and quantitative data were collected, and the two projects were compared based on five performance metrics: total cost growth; cost per square foot; total schedule growth; construction intensity; and change-order factor. The results showed that the DB project did not compare as favorably regarding the metrics used. Also, the level of collaboration effort and the use of BIM significantly improved the performance of the IPD project. By understanding the delivery methods and comparing them, owners can make an informed decision when choosing delivery methods for similar projects. As a recommendation, the study suggests the use of a more rigorous statistical analysis to determine whether the same findings hold true.